Short-Term Effect of Gastric Resection on Circulating Levels of Ghrelin, Peptide YY3–36 and Obestatin in Patients with Early Gastric Cancer - Jeon, T. Y.; Lee, S. Y.; Kim, H. H.; Cho, Y. H.; Cho, A. R. (Hormone and Metabolic Research, 2015)
The short-term responses of gut hormones and the compensative interaction during a one-week period after subtotal gastrectomy in early gastric cancer (EGC) patients were assessed. Previous studies have reported gut hormonal changes after Roux-en-Y gastric bypass surgery. Blood samples were collected from 40 patients with EGC preoperatively, at 1 h after gastric resection, and on postoperative day (POD) 1, 3, and 7. Levels of active ghrelin, total ghrelin, obestatin, and PYY3-36 were measured. Total ghrelin level rapidly reached a nadir of 69.1%, while active ghrelin level had increased to 135.5% at 1 h after resection. Then, both returned to preoperative level. On the contrary, active/total ghrelin reached its nadir quickly at 1 h after resection and had returned to the preoperative level by POD 3. The nadir PYY3-36 level was 71.4% on POD 1, followed by a gradual recovery, and had increased to 116.5% by POD 7. The same pattern was observed for obestatin. Active ghrelin/obestatin showed an increase on POD 1 while total ghrelin/obestatin showed a decrease on POD 3. Then, both returned to preoperative level. These results suggest that a rapid interactive compensatory mechanism of gut hormones does exist in the remnant gastrointestinal tract after abrupt changes in the production reservoir in nonobese people.
Keywords: ghrelin; peptide YY3-36; obestatin; stomach; gastrectomy